STUTTERING LANGUAGE DISORDER OF STAND-UP COMEDIAN OFF-STAGE SPEECH - Ainun Rahmania Saputri (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aims to analyze the type of stuttering found in a stand-up comedian's speech when speaking offstage. It used a descriptive qualitative method. The theoretical concept used is from Carrol (1986) on the types of language disorders and it adapted the theoretical framework of Handoko (2014) and Saragih (2018) to analyze the types and the occurrence of stuttering language disorder. Based on the results of the analysis, there are two kinds of expressive language disorders found in namely fluency disorder and voice disorder. Fluency disorder occurs in the form of repetition, prolongation, interjection, and pause. The type of stuttering mostly found is repetition. There is no characteristic of circumlocution stuttering. In addition to bringing up the types of individual characteristics, the utterances also show combinations of voice disorders.